Cambodia's curse : the modern history of a troubled land - Brinkley, Joel, 1952- (New York : PublicAffairs, 2011)
Nobel Prize winning reporter Joel Brinkley illuminates the country, its people, and the deep historical roots of its modern-day behavior.
Includes bibliographical references (p. 367) and index.
Keywords: Pol Pot -- Influence; Democracy -- Cambodia; Social change -- Cambodia; Cambodia -- History -- 1979-1993.; Cambodia -- History -- 1993-; Cambodia -- Politics and government -- 1979-1993.; Cambodia -- Politics and government -- 1993-; Cambodia -- Social conditions -- 21st century